2011
DOI: 10.2337/dc10-2105
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Intensive Therapy in Newly Diagnosed Type 2 Diabetes Partially Restores Both Insulin Sensitivity and β-Cell Function in Subjects With Long-Term Remission

Abstract: OBJECTIVETo examine the effect of intensive glycemic control therapy (IT) on insulin sensitivity and β-cell function in newly diagnosed type 2 diabetic patients compared with subjects with normal glucose tolerance (NGT) and those with impaired glucose tolerance (IGT).RESEARCH DESIGN AND METHODSForty-eight newly diagnosed type 2 diabetic patients were randomly assigned to IT for 2 weeks and followed up for 1 year. Intravenous glucose tolerance tests were conducted in NGT, IGT, and diabetic subjects. Blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 25 publications
6
76
1
Order By: Relevance
“…This study was an observational follow-up and expansion of the previously published intensive IT (17) conducted at the Nanjing Drum Tower Hospital between September 2009 and August 2012. Based on World Health Organization 1999 diagnostic criteria, 80 (67 men and 13 postmenopausal women) newly diagnosed type 2 diabetic subjects with hyperglycemia (HbA1c R8%) participated in the study.…”
Section: Subjects and Research Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was an observational follow-up and expansion of the previously published intensive IT (17) conducted at the Nanjing Drum Tower Hospital between September 2009 and August 2012. Based on World Health Organization 1999 diagnostic criteria, 80 (67 men and 13 postmenopausal women) newly diagnosed type 2 diabetic subjects with hyperglycemia (HbA1c R8%) participated in the study.…”
Section: Subjects and Research Designmentioning
confidence: 99%
“…We and others have demonstrated that short-term insulin intensive therapy (IT) is effective to reduce hyperglycemic-induced insulin resistance (17,18). As insulin resistance would be reduced whereas circulating insulin level is not decreased or even increased during IT, we hypothesized that IT would be an optimal regimen to determine whether it is the reduction of insulin resistance or circulating insulin per se that is responsible for serum SHBG elevation.…”
Section: Introductionmentioning
confidence: 99%
“…15 The UKPDS findings and the potential cardioprotective effects of insulin [16][17][18] suggest that early provision of sufficient basal insulin to normalize fasting plasma glucose levels may safely reduce incident cardiovascular outcomes. Evidence that exogenous insulin may slow the decline in pancreatic function with time [19][20][21] suggests that such an intervention may also reduce incident diabetes in people at risk for the disease. These hypotheses were tested in the present study, the Outcome Reduction with an Initial Glargine Intervention (ORIGIN) trial, 22 which involved people 50 years of age or older with impaired fasting glucose, impaired glucose tolerance, or early type 2 diabetes in addition to other cardiovascular risk factors.…”
mentioning
confidence: 99%
“…The strategy of providing short-term intensive insulin therapy (IIT) early in the course of T2DM has been tested in previous clinical studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In most of these studies, the goal of this treatment strategy was the induction of "remission" of diabetes, defined variably as the subsequent maintenance of normoglycemia without any anti-diabetic therapy after cessation of the initial IIT.…”
Section: Short-term Intensive Insulin Therapy In Early Type 2 Diabetesmentioning
confidence: 99%